Perceived Position of the National TV Broadcasters in the Republic of Macedonia - Ciunova-shuleska, Anita (My University, 2007)
The aim of this paper is to give clear picture of the position that national TV broadcasters in the Republic of Macedonia hold, as it is perceived by the viewers i.e. citizens of the Republic of Macedonia. Currently in the Republic of Macedonia operate 6 national TV broadcasters out of which one broadcaster operates as a public broadcasting company and five operate as commercial broadcasting companies. On the basis of а survey conducted on 53 people age above 18 who filled in a questionnaire constructed on the basis of а scale from 1 to 9, the positioning map is constructed showing that some of the national TV broadcasters have good position in the customers’ eyes whereas some of them have bad perceived position which demand appropriate marketing activities to be taken. The results show that the position of each TV broadcasting company differs and is driven by 4 general variables: modern, old-fashioned (obsolete), oriented towards political issues and national interests, oriented towards entertainment and technological issues while other variables used in the survey play fundamental role in determination of the above-mentioned 4 general variables for map construction.
Keywords: positioning map, perceived position, national TV media